A Catechism on Biblical History in the Aramaic Dialect of Mosul Abrégé d'histoire sainte en langue chaldéenne vulgaire - Anonymous, Anonymous (Syriac Studies Library, 2011)
This volume provides an overview of biblical history in the form of questions and answers in the modern Aramaic dialect of Mosul